2019
DOI: 10.1155/2019/9319480
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Preoperative Opioid Use Disorder on Complications and Costs following Primary Total Hip and Knee Arthroplasty

Abstract: Introduction. Multiple studies have demonstrated that patients taking opioids in the preoperative period are at elevated risk for complications following total hip (THA) and knee (TKA) arthroplasty. However, the incidence and impact of opioid use disorder (OUD) among these patients—both clinically and fiscally—remain unknown. The purpose of this study was to investigate this relationship. Methods. The Nationwide Readmission Database (NRD) was used to identify patients undergoing THA and TKA from 2011 to 2015. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…The survey we used attempted to quantify patient-reported disease severity, perceptions related to surgical delays, and the implications that this may have with regard to their willingness and eagerness to reengage the healthcare system. Some of our questions were derived from prior, similar studies [34, 35], while others were aimed at addressing potential provider concerns [30, 39]. While some patients reported multiple pain generators, we explicitly asked that they attempt to isolate perceptions of their pre-surgical joint.…”
Section: Methodsmentioning
confidence: 99%
“…The survey we used attempted to quantify patient-reported disease severity, perceptions related to surgical delays, and the implications that this may have with regard to their willingness and eagerness to reengage the healthcare system. Some of our questions were derived from prior, similar studies [34, 35], while others were aimed at addressing potential provider concerns [30, 39]. While some patients reported multiple pain generators, we explicitly asked that they attempt to isolate perceptions of their pre-surgical joint.…”
Section: Methodsmentioning
confidence: 99%
“…Quality of life (Short-Form 36) was found to be approximately two standard deviations below normal population scores. It is also well known that patients waiting for hip or knee arthroplasty are often prescribed opioids, leading to increased postoperative opioid tolerance, potential opioid addiction, increased perioperative complication rates and overall costs [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…8,9,40,41,44 Concerning total joint arthroplasty, numerous publications have cited preoperative and perioperative opioid use as risk factors for deleterious outcomes after surgery, noting increased health care utilization and increased rates of prosthetic joint infection and revision surgery. 4,6,7,20,56,59 Similar studies have also identified preoperative opioid use as a negative predictor of patient-reported outcome measure scores, with lower preoperative baseline scores and lower overall change in function after arthroplasty. 12,31,32,33,50 A similar relationship has been found in patients undergoing RCR.…”
mentioning
confidence: 78%
“…In light of the opioid epidemic, 54 discerning the effect of opioid use on patient outcomes is paramount. While previous studies have addressed the effect of preoperative opioid use on the development of postoperative complications in numerous general and orthopaedic surgical procedures, 3,6,7,56,59 researchers know little about this relationship in patients undergoing RCR. Specific to RCR, existing literature has focused on the effect of preoperative opioids on patient-reported outcomes, finding less robust improvements in patient-reported outcome measure scores in opioid use groups.…”
Section: Discussionmentioning
confidence: 99%